Olanzapine-Induced Hyperprolactinemia: Two Case Reports - Barata, Pedro Cabral; Santos, Mário João; Melo, João Carlos; Maia, Teresa (Frontiers in Pharmacology, 2019)
Background: Hyperprolactinaemia is a common consequence of the treatment with antipsychotics. It is usually defined by a sustained prolactin level above the laboratory upper level of normal in conditions other than that where physiologic hyperprolactinaemia is expected. Normal prolactin levels vary significantly among different laboratories and studies. Several studies indicate that olanzapine does not significantly affect serum prolactin levels in the long term, although this statement has been challenged. Aims: our aim is to report two olanzapine-induced hyperprolactinaemia cases observed in psychiatric consultations. Methods: medical record analysis of the patients who developed this clinical situation observed in psychiatric consultations in the Psychiatry Department of the Prof. Dr. Fernando Fonseca Hospital during the year of 2017, complemented with a non-systematic review of the literature. Results: the case reports consider two women who developed prolactin-related symptoms after the initiation of olanzapine. No baseline prolactinaemia was obtained, and prolactin serum levels were only evaluated after prolactin-related symptoms developed: at the time of its measurement, both patients had been taking olanzapine for more than 24 weeks. Hyperprolactinaemia was found to be present in Case 2, whereas Case 1 (a 49-year-old woman) had “normal” serum-prolactin levels for premenopausal and prolactin levels slightly above the maximum levels for postmenopausal women. Both patients underwent similar pharmacological adjustments, which comprised switches from olanzapine to aripiprazole. After all pharmacological changes, prolactin serum levels decreased to normal range values and prolactin-related symptoms disappeared. Discussion/Conclusions: Laboratorial and literature prolactinaemia values variability and discrepancies may difficult the management of borderline hyperprolactinaemia clinical situations. Baseline prolactin levels collection should have been obtained, as they help in the management of patients who develop neuroleptic-induced hyperprolactinaemia. Prolactin-related symptoms can occur with borderline or normal standardized prolactinaemia values. Olanzapine-induced hyperprolactinaemia is a rare but possible event. Aripiprazole was used as a suitable alternative for olanzapine-induced hyperprolactinaemia.